Kedudukan Hukum Kontrak Spot dalam Transaksi Kripto di Indonesia - Andika Rayhan Putra Herang; Nirwan Junus; Mellisa Towadi (Lembaga Yasin AlSys, 2026)
Spot market transactions in crypto assets in Indonesia have shown significant growth; however, this development has not been fully matched by adequate legal certainty and protection, particularly regarding the legal status of spot contracts as the basis of the legal relationship between business actors and consumers. This study aimed to analyze the legal status of spot contracts in crypto-asset transactions in Indonesia and to identify factors influencing their implementation under spot market supervisory provisions, an urgency heightened by the rapid growth of crypto-asset trading and the shift in the supervisory regime from the Commodity Futures Trading Regulatory Agency (Bappebti) to the Financial Services Authority (OJK). The study employed normative legal research using a statutory approach and a comparative approach. The findings show that spot contracts have a valid and binding legal status because they satisfy the legal requirements for agreements under Article 1320 of the Indonesian Civil Code (KUHPerdata) and are executed through organizers registered with and supervised by the competent authority. The transfer of authority from Bappebti to OJK marks a paradigm shift from viewing crypto assets as commodities toward treating them as digital financial assets under financial services sector supervision. The study also finds that the effectiveness of spot contract implementation is determined by three main factors: regulatory consistency, supervisory effectiveness, and institutional readiness, including the governance of exchanges, physical traders, and clearing institutions, which are essential prerequisites for ensuring legal certainty, market stability, and consumer protection within Indonesia’s crypto-asset trading ecosystem. Accordingly, this study has implications for strengthening understanding of electronic contracts in the context of digital financial assets and enriching scholarship on the legal status of spot contracts within the Indonesian legal system.